Effect of various electrophoretically deposited nano‐silica contents on the properties of poly(vinylidene fluoride‐co‐hexafluoropropylene)‐based electrospun polymer electrolytes. Issue 2 (9th December 2015) - Xiao, Wei; Miao, Chang; Yan, Xuemin; Mei, Ping
Abstract: Poly(vinylidene fluoride‐ co ‐hexafluoropropylene) (P(VDF‐HFP)) based composite polymer electrolyte (CPE) membranes were successfully prepared by electrospinning followed by electrophoretic deposition processes, and desirable polymer electrolytes were obtained after being activated in liquid electrolytes. The physicochemical properties of the CPEs with different electrophoretically deposited nano‐SiO2 contents were investigated by SEM, XRD, TGA, linear sweep voltammetry and electrochemical impedance spectroscopy measurements. When the ratio of electrophoretically deposited nano‐SiO2 to P(VDF‐HFP) is up to 4 wt%, the results show that the CPE membrane presents a very uniform surface with abundant interconnected micropores and possesses excellent mechanical tensile strength with high thermal and electrochemical stability; the ionic conductivity at room temperature can reach 3.361 mS cm −1 and the reciprocal temperature dependence of the ionic conductivity follows a Vogel − Tamman − Fulcher relationship. The interfacial resistance of the assembled Li/CPE/Li simulated cell can rapidly increase to a steady value of about 950 Ω from the initial value of about 700 Ω at 30 °C during 15 days' storage. The battery performance test suggests that the CPE also shows excellent compatible properties with commercial LiCoO2 and graphite materials. © 2015 Society of Chemical Industry Abstract : Nyquist plots of symmetrical Li/CPEs with different nano‐SiO2 electrophoretic deposition content/Li cells with various storage times at 30 °C, where the insert shows the corresponding equivalent circuit for each Nyquist plot (A: 0 wt. %; B: 2 wt. %; C: 4 wt. %; D: 6 wt. %)